The Attitude And Perception Of Medical Students Towards Basic Sciences During Their Clinical Years - Bhusal, Pujan; Yadav, Ram Lochan; Khatiwada, Sushma; Timilsina, Sameer; Sapkota, Niroj Khatri (Journal of Karnali Academy of Health Sciences, 2022)
Background: Basic sciences subjects are taught in the first two years of the medical course. They are considered the base for understanding the pathophysiological process of disease and accurate patient care. The study was done to assess the attitude and perception of the students regarding the course content, recall, and relevance of basic science knowledge in their clinical years. Methods: This descriptive cross-sectional study was conducted among medical students in their clinical years at Chitwan Medical College, Nepal from September 2020 to December 2020. The self-administered questionnaire targeted medical students in their clinical years to collect the data. The descriptive statistics were applied using IBM SPSS V.20 for analyzing data. Results: Out of 180, a total of 151 (83.88%) students participated in this study. The study revealed that pathology had the vastest syllabus. About 72.18% (109) of students agreed that pharmacology is the most important subject to be a good clinician. Moreover, many of them added pharmacology 71% (107) and anatomy71.52% (108) along with pathology as the most needful subject among basic sciences to deeply understand the diseases and their management. Few respondents mentioned Microbiology 34% (51) and biochemistry 27.15% (41) curriculum should cover only the general concepts to give the working knowledge of the subject. Conclusion: Overall, the student’s attitudes and perceptions regarding the basic science subjects in their clinical years were found to be highly affirmative pointing to the relevance of basic science subjects in understanding and solving the clinical problems. Keywords: , , , .